METHODICAL SYSTEM OF STUDENT-TEACHERS TRAINING FOR TEACHING MATHEMATICS - Skvortsova, Svitlana (Mountain School of Ukrainian Carpaty, 2020)
The current stage of development of the system of higher pedagogical education in Ukraine requires updating the methodological system of training future teachers to teach mathematics to learners. Already today, students of 1st-2nd grades study according to the new State Standard of Primary General Education, the draft Standard of Basic Secondary Education is awaiting approval, the draft Professional Standard for Professions “Primary School Teacher of General Secondary Education Establishment”, “Teacher of General Secondary Education Establishment” have been presented for public discussion on the Ministry of Education and Science website. The purpose of methodological training of future teachers is to form in them methodical competence, which is understood as internal personal education, which is manifested in the ability and capability to effectively solve standard and problematic methodological problems, based on theoretical and practical readiness to perform the function of teaching a subject or an integrated course. Based on the essence of the methodological activity of the teacher, methodical competence is considered by us as a system of components, among which – normative, variable, special-methodical, control-evaluation, technological and design-modeling. Thus, the content of the methodological system of training future teachers should be aimed at the formation of each of these components in students. It is obvious that at the present stage of development of the education system of Ukraine, in order to achieve the goal of training future teachers – the formation of methodical competence in them, the content, form and technology of teaching need to be updated. Based on the fact that elementary school learners are already representatives of the digital generation, who have acquired an excessive ability to absorb digital information, who are from an early age in two worlds – physical and virtual, the content of methodological disciplines should be expanded to use ICT in teaching learners mathematics. Based on the current need in the use of ICT in the learning process, the possibility of acquiring methodological competence not only in formal education but also in the process of non-formal and informal education, the methodological system of training has acquired updates and forms of learning. In addition, ICT should not only be the subject of study for student-teachers, but also be widely used directly in the training of future professionals. Therefore, we have improved the technological unit of the methodological system. Thus, the article proposes an update of the developed by the author structural and functional model of training future teachers to teach mathematics to learners, in the block “Methodical system of training student-teachers to teach mathematics to learners”.